2011
DOI: 10.1111/j.1365-2966.2011.18799.x
|View full text |Cite
|
Sign up to set email alerts
|

Tidal disruption of NEAs - a case of Příbram meteorite

Abstract: This work studies the dynamical evolution of a possible meteor stream along the orbit of the Příbram meteorite, which originated in the tidal disruption of the putative rubble-pile-like parent body during a close approach to the Earth. We assumed the disruption at the time when the ascending or descending node of the parent orbit was close to the Earth's orbit. In the last 5000 yr, the Příbram orbit has crossed the Earth orbit twice. It happened about 4200 and 3300 yr ago. In both cases, we modelled the releas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 29 publications
(50 reference statements)
1
17
1
2
Order By: Relevance
“…Walsh et al 2008) or tidal stresses (see e.g. Tóth et al 2011). These last three processes can easily produce secondary fragments.…”
Section: Comparative Dynamics and Discussionmentioning
confidence: 99%
“…Walsh et al 2008) or tidal stresses (see e.g. Tóth et al 2011). These last three processes can easily produce secondary fragments.…”
Section: Comparative Dynamics and Discussionmentioning
confidence: 99%
“…Mild tidal events might be also capable of producing meteoroid streams. The close passage of an object by a planet can lift material from the surface that then spreads along the object's orbit with time due to the small ∆v imparted by the lifting process and gravitational perturbations by other objects in the solar system (Kornoš et al 2009;Tóth et al 2011). After hundreds of years the particles will be distributed along the entire orbit and will produce meteors and fireballs if they enter Earth's atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the single-event nature of the tidal disruption the stream would not be replenished and the putative meteoroid stream could only be observed for a short time after creation. Tóth et al (2011) calculated the maximum activity of a meteor shower originating from the putative Pribram meteorite progenitor to be only 1 meteor in 8 days visible from a single observing place. Richardson et al (1998) performed numerical simulations of NEO distortion and disruption by Earth's tides using more realistic asteroid shapes, spin rates, axis orientations, perigee distance q, relative speed at infinity v ∞ and body orientation at periapse, and identified four classes of tidal encounter outcomes (that should not be confused with the capital letters used to identify asteroid taxonomic classes): s) catastrophic disruptions in which the largest remaining fragment retains less than 50% of the parent's mass (similar to SL9), b) rotational breakup in which the largest remaining fragment retains 50%-90% of the parent's mass, m) mild disruption in which less than 10% of the parent's original mass is lost and, n) no mass loss but possible morphological modification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its encounter with the gravity of the Earth-Moon system may have shed off substantial amounts of asteroid debris already at distances of 10,000-20,000 km from Earth. Asteroids entering within the Roche limit get affected by tidal gravity, and anything between loss of surface material to complete disruption of the asteroid may happen (Richardson et al, 1998;Nesvorný et al, 2010;Tóth et al, 2011;Schunova et al, 2014;Yu et al, 2014). Recent space missions to asteroids Itokawa and Eros (mean diameters 0.3 and 17 km, respectively) have shown that small to large asteroids have a significant layer of lose regolith or "rubble-pile" debris on their surface (Murdoch et al, 2013).…”
Section: Discussionmentioning
confidence: 98%